The New Religious Consciousness - Bellah Robert N.; Glock Charles Y (University Of California Press, 1976)
The best analysis of the growing new religious movements. Foreword, Preface, New Religious Movements in the Asian Tradition, New Quasi-Religious Movements, New Religious Movements in the Western Tradition, The Response of the Established Religions, The Survey, The New Religions in Social Context, Historical Perspective, Religious Change in Nineteenth-Century America, Conclusions, About the Contributors, Index.